2016
DOI: 10.5812/hepatmon.37011
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis C Virus Core Amino Acid 70 Substitution and Genotypes of Polymorphisms Near the IFNL3 Gene in Iranian Patients With Chronic Hepatitis C

Abstract: BackgroundMolecular studies have demonstrated that the hepatitis C virus (HCV) genotype and host genetics play predictive roles in the management of patients infected with HCV.ObjectivesThis study aimed to investigate the HCV genotype, core amino acid (aa) 70 substitution, and polymorphisms near the IFNL3 gene (including rs12979860 and rs8099917) among Iranian patients with chronic hepatitis C (CHC).Patients and MethodsIn this cross-sectional study, the molecular profiles of the HCV genotype, core aa 70 substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…In Iran, HCV genotype 1 is the most prevalent HCV isolate (17,18). Moreover, HCV genotype 1 was the most isolated genotype from Iranian thalassemia patients with HCV infection (19). However, a previous study in Sistan and Baluchistan found HCV genotype 3 as the dominant genotype in children and adolescents with thalassemia major (20).…”
Section: Discussionmentioning
confidence: 98%
“…In Iran, HCV genotype 1 is the most prevalent HCV isolate (17,18). Moreover, HCV genotype 1 was the most isolated genotype from Iranian thalassemia patients with HCV infection (19). However, a previous study in Sistan and Baluchistan found HCV genotype 3 as the dominant genotype in children and adolescents with thalassemia major (20).…”
Section: Discussionmentioning
confidence: 98%
“…The different pattern of HCV infection in Iranian hemophiliac patients has been clearly defined. Previously, it was shown that HCV-1b is more frequently observed in Iranian hemophiliac patients than other Iranian HCV infected groups (57). This may indicate the possible similarity of HCV-1b of Iranian and European isolates and suggests an infection through blood products such as clotting factors imported to Iran.…”
Section: Discussionmentioning
confidence: 99%
“…On samples with con rmed positive antibody, quantitative HCV RNA test (The Artus HCV RG RT-PCR Kit, Qiagen) and genotyping were performed by reverse transcription-polymerase chain reaction (RT-PCR) followed by sequencing (26). Sample collection procedures have been previously detailed elsewhere (27).…”
Section: Sample Collectionmentioning
confidence: 99%